Evaluating writing skills at the university level using rubrics - Darawsheh, Salah Al-din Ahmad (Journal of Educational and Psychological Sciences, 2020)
The purpose of this study is to determine how to evaluate writing skills using rubrics. Mainly, it attempted to answer the following questions: What is a rubric? What are the rubric types? What are their strength and weakness points? How to prepare a rubric? What scales are proposed to judge writing? A descriptive-analytic approach was used. The results revealed that writing could be better measured by rubrics, and that makes judgements more accurate and reliable.